USING GUESSING GAME WITH KAHOOT APPLICATION TO IMPROVE CHILDREN VOCABULARY MASTERY - Nur Farisda; Muthmainnah Mursidin; Sitti Nurjannah (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2025)
This study aimed to examine the effectiveness of using a guessing game through the Kahoot application to improve vocabulary mastery among kindergarten children. The research was conducted at TK Dharma Wanita UNHAS, involving children from group B2 as participants. The study employed a pre-experimental design using a one-group pre-test and post-test model. The vocabulary materials covered in this study focused on four main themes: colors, animals, fruits, and numbers. These topics were selected based on their relevance and familiarity to early childhood learners. The pre-test results showed that most students were in the "Not Yet Developed" (30%) and "Starting to Develop" (35%) categories. In contrast, the post-test results showed that none of the students remained in the "Not Yet Developed" category. A total of 50% of students reached the "Developed Very Well" category, indicating a significant improvement after the implementation of the guessing game with the Kahoot application. The students' average scores also increased from 47.5 to 80. In conclusion, the findings suggest that the use of Kahoot-based guessing games is an effective teaching strategy for enhancing vocabulary mastery among kindergarten children. It creates a fun, interactive, and motivating learning environment, which is essential for young learners in acquiring new improving vocabulary.